Reliability of a Battery of cognitive tests in Young, healthy people - Ramírez-delaCruz M,; Bravo-Sánchez A,; Esteban-García P,; Jiménez F ,; Abián-Vicen J, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Cognitive performance is an essential aspect of sports. Still, few studies provide reliable cognitive tests for training and evaluating cognitive aspects related to sports, particularly in a healthy and/or youthful population. This study assessed the intraday and interday reliability of a cognitive test battery related to sports performance. In the research, seventeen healthy volunteers participated. DynavisionTMD2, Bassin Anticipation Timer, Go/No-Go, Eriksen Flanker, and the Trail Making Test (TMT) were analyzed. TMT-A and TMT-B (intraday), as well as the following variables in the interday analysis, exhibited significant differences: "Physical RT - Fastest" (Test 1), "Visual RT - Fastest" and "Physical RT - Fastest" (Test 2), "Visual RT - Fastest" (Test 4) and TMT-A. Thirteen of the thirty-one variables analyzed on the intraday exam had moderate Intraclass Correlation Coefficients (ICC), six were good, and one was exceptional. In the interday analysis, 15 variables with moderate ICC and 5 variables with excellent ICC were identified. Reliable tests include "Reaction Time" (Tests 5 and 6) and "Red and Green Lights" of the DynavisionTMD2, the 15 mph speed of the Bassin Anticipation Timer, and the Go/No-Go, Eriksen Flanker, and TMT tests.